Seamless Integration of ROS2 Topics and FPGA via UART: Developing an Easy Integration Layer - Sant’Anna, Tiago B.; Oliveira, João A. C. B.; Lima, Rebeca T. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
This article presents an integration approach for real-time sensor data processing using Field Programmable Gate Arrays (FPGAs) and the Robotic Operating Systems (ROS). By developing a VHDL-based computational system, the study focuses on simplifying the data processing for sensors within the ROS framework. The validation of computer-to-FPGA communication, sensor data reading in ROS, and the establishment of communication between ROS and the FPGA are discussed. The results demonstrate successful integration using UART protocol, showcasing the potential of FPGAs to address latency and energy consumption issues. Future plans include expanding communication methods, dynamic reconfiguration, and comparing processing techniques. This work contributes to advancing sensor data processing capabilities in robotics applications.